Effectiveness of standard cervical physiotherapy plus diaphragm manual therapy on pain in patients with chronic neck pain: A randomized controlled trial. (April 2021) - Simoni, G.; Bozzolan, M.; Bonnini, S.; Grassi, A.; Zucchini, A.; Mazzanti, C.; Oliva, D.; Caterino, F.; Gallo, A.; Da Roit, M.
Abstract: Background: Literature concerning the effect of diaphragm treatment to reduce neck pain symptoms is scarce. Aim of this trial was to investigate the effects of diaphragm manual therapy associated with standard physiotherapy treatment on pain in patients with Chronic Neck Pain (CNP). Methods: In a private practice clinic, subjects with CNP were randomly assigned to receive three 30-min treatment sessions of standard cervical physiotherapy and Diaphragm Manual Therapy (DMT) or Sham Diaphragm Technique (SDT). Participants and assessors were blinded to the assignment. Primary outcome was pain, secondary outcomes were cervical active range of motion, pain pressure threshold, disability and quality of life measured at baseline, before and after each session, at 3 and 6-months. Adverse events were monitored. A non-parametric multivariate approach (combined permutation test) was applied to assess the effect of the treatment on all the outcomes. An intention to treat analysis was performed. Results: Forty patients were randomly allocated to DMT and SDT groups. Combined permutation test showed a significant higher improvement in DMT group compared to SDT group (p-value = 0.0002). The between-group comparisons on single outcomes showed a statistically significant improvement only for pain pressure threshold on upper trapezius (adjusted p-value = 0.029). No adverse events related to the intervention were registered. Conclusions: In patients with CNP, addition of diaphragm manual techniques to standard cervical treatment seems to give a better global outcome, but this improvement is of unclear clinical relevance; the primary outcome seems not to have a role. Further studies are needed to confirm and clarify these results. Trial registration: Release Date: July 18, 2017 Registered in ClinicalTrial.gov database ID: NCT03223285A. Highlights: Diaphragm manual treatment report a small positive effect on overall functioning. First trial assessing diaphragm manual treatment effect in patient with chronic neck pain. No Side effects were registered in the diaphragmatic manual treatment group. Diaphragmatic manual treatment is low cost and comfortable. Innovative statistical method that calculate a global p-value that combines all outcomes.